Brain-Actuated Control of Dual-Arm Robot Manipulation With Relative Motion - Li, Zhijun; Yuan, Wang; Zhao, Suna; Yu, Zhenzhong; Kang, Yu; Chen, C. L. Philip (IEEE transactions on cognitive and developmental systems, 2019)
This paper describes the brain-actuated control of a dual-arm robot performing bimanual relative motion manipulation tasks, through the adoption of relative Jacobian matrix, wherein the dual-arm robot can be considered as a single manipulator and the movements of the end effectors can be calculated by the relative motion. An online brain-machine interface (BMI) system based on multichannel steady-state visual evoked potentials was developed, and it was able to perform band-pass filtering and visual stimuli classification using support vector machines. Considering the relative motion in a constrained plane, the asymmetric bimanual manipulation can be transformed into 2-D control tasks through polar coordinate transformation such that the end effectors can achieve smooth direction-and-distance motion in the arbitrary position of the operational space. Moreover, the kinematics redundancy scheme, using online neuro-dynamics optimization, was developed for joint velocity optimization subject to physical constraints. Five individuals participated in the experiments and successfully fulfilled the given manipulation task.